Świadectwo Pism o Jezusie w Ewangelii Janowej - Nalewaj, Aleksandra (Verbum Vitae, 2015)
The subject of the present study is the words of Jesus presented in John 5:39: “You search the Scriptures because you think that in them you have eternal life; and it is they that bear witness about Me.” A larger apologetic speech of Jesus constitutes the immediate context of this statement; within the structure of the Fourth Gospel this discourse follows the description of the healing of the paralytic at the Bethesda Pool (cf. John 5:1-47). The monologue is the response of Jesus to certain Jews who strongly objected to his activity during the Sabbath day and to Jesus’ likening himself to the Father. Exchanging arguments in his own defence, Jesus quotes the testimony of the Scriptures. Investigation of the Old Testament texts clearly points to Jesus, and thus His claims to take action on a holy day are fully justified.